The 1st international workshop development of renewable energy for the Mekong Delta : (Can Tho University, 2016)
The workshop will provide an interdisciplinary forum for the discussion of advances in the science and technology of clean and renewable energy development in the Mekong Delta and build network with the scientists and engineers from different countries.